Bio-inspired hydrophobic/cancellous/hydrophilic Trimurti PVDF mat-based wearable triboelectric nanogenerator designed by self-assembly of electro-pore-creating. (July 2019) - Zhang, Jia-Han; Li, Yong; Du, Jinhua; Hao, Xihong; Wang, Qing
Abstract: Electrical performances, output stability and use of comfort are three crucial indexes for the rapid advancements in wearable power generators. However, there exist few studies that can simultaneously improve the three aforementioned indexes in a simple manner. Here, a bio-inspired Trimurti poly(vinylidene fluoride) (PVDF) tribo-material with a transcendent electrical performance, excellent output stability in high environmental humidity, and increased use of comfort under a sweating condition is designed, by simple self-assembly of electro-pore-creating. The nanoporous cancellous-bone-like, hydrophobic lotus-leaf-like, and hydrophilic root-xylem-like structures are assembled respectively in the interior, on the upper surface and on the bottom surface of Trimurti PVDF mat, endowing the fabricated Trimurti triboelectric nanogenerator (T-TENG) with outstanding electrical performances and availability in different application environments. With a high power density of 10.6 W m −2, the T-TENG can directly drive 714 light-emitting-diodes and small electronics. Additionally, under the relative humidity of 85%, the output retention rate of the T-TENG reaches up to 22%. Under the simulated sweating condition, the Trimurti PVDF mat can absorb sweat into its bottom region to accelerate evaporation of sweat. This work indicates a substantial progress of wearable high-performance power sources for dealing with various complex conditions in practical applications. Graphical abstract: A bio-inspired Trimurti tribo-material with nanoporous cancellous-bone-like, hydrophobic lotus-leaf-like, and hydrophilic root-xylem-like structures is designed via a simple, low-cost, and easily scalable electro-pore-creating method, which endows the fabricated Trimurti TENG as a wearable power supply with great electrical performances, excellent output stability in high environmental humidity, and increased use of comfort under a sweating condition. Image 1 Highlights: A Trimurti tribo-material with three heterogenous structures is designed by an innovative electro-pore-creating method. The thickness and the average pore size of the Trimurti tribo-material are only 12 μm and 300 nm, respectively. The Trimurti TENG possesses great electrical performances, output stability, and use of comfort. The Trimurti TENG can replace the chemical battery to drive electronics within a few seconds under gentle finger tapping.